Pelatihan Pengelolaan Sampah Rumah Tangga di Desa Dawung Kabupaten Magelang - Annis Azhar Suryaningtyas; Aditama Bulan Pratiwi; Pratiwi Amalia Ramadhani; Nurhafidzah Nurhafidzah; Yuhan Shalahudin Alayyubi; Nafica Septy Anggraeni; Aftina Nurul Husna (Universitas Muhammadiyah Semarang, 2023)
Its was recorded that in 2019 the residents of Magelang Regency produced 580 tons of waste. This fact illustrates that waste is still a problem in Magelang Regency, including in Dawung Village. Waste management with the principles of reduce, reuse and recycle (3R) offers a solutiom to alleviating waste problems. howwver, its implementation is still not optimal. The reason, not evenly distributed public insight about the discourse. Therefore, programs to strengthem communjty knowledge relate to 3R waste management and waste management into gooda with new values are interesting to implement. There are four strages of implementing this community service peogram namelu situatiok analysis, planning, implementation, and evaluation. The result of the implementation of this program is that Dawung Village residents’ insights have opened up about the 3R waste managemen proses and enriched residents’ skills in managing waste into goods with new value.